Material culture: A digital documentation of the art and culture of the Saribas Malay, Sarawak - Faridah, Sahari; Rahah, Hasan; Lucas, Terry (2018)
This paper investigates the use and application of material culture study methods to document and organize the cultural collections of Saribas Malay society in Betong Division, Sarawak Borneo. The main objective of the study is to provide documentation template based on the material culture theory to preserve and sustain the cultural objects, starting with a practical approach in which the application can be easily and effectively implemented by the local community. In-depth interview is the method applied in this qualitative research to gather data on respondents’ awareness on the importance of documenting material culture and their perception towards the application of documentation template. The Fleming’s (1974) and Prown’s are adapted to construct the template to document information of the artefacts and as analysis tools. The finding from the interview sessions with the Saribas community shows a positive indication towards the effort to preserve material culture through documentation and simple template proposed is said to be sufficient to record the basic information of their made, used and possessed artefacts. Although this attempt will take time to be fully implemented, but in the long run, this practice will be able to create a valid documentation that allows it to be used as reference for academic, museum cataloguing and antique collection purposes.